Нужно найти производную сначала ее вычислить а потом подставить x
Пишите задание понятно и исчерпывающе!
f(x)=корень(x^2-2x)
f'(x)=(корень(x^2-2x))'=1/(2*корень(x^2-2x)) *(x^2-2x)'=(2x-2)/(2*корень(x^2-2x))=
=(x-1)/корень(x^2-2x)
f'(3)=(3-1)/корень(3^2-3)=2/корень(6)=2*корень(6)/6=корень(6)/6
f(x)=корень(x^2+1)
f'(x)=(корень(x^2+1))'=1/(2*корень(x^2+1))' *(x^2+1)'=2x / (2*корень(x^2+1))=
=x/корень(x^2+1)
f'(2)=2/корень(2^2+1)=2/корень(5)=2/5*корень(5)
f(x)=(x^2+1)*под корнем x^2+1=(x^2+1)^(3/2)
f'(x)=( (x^2+1)^(3/2) )'=3/2 *(x^2+1)^(3/2-1) * (x^2+1)'=3/2 *корень(x^2+1)* 2x=
=3x*корень(x^2+1)
f'(корень(3))=3*корень(3) *корень((корень(3))^2+1)=
=3*корень(3)*2=6*корень(3)
627 300, 3 800 004, 400 070 206, 95 308 600 745, 10 100 075 003, 9 000 005 006
1 км = 10 000 дм
50 см = 5 дм
230 см = 23 дм
67 м = 670 дм
800 м = 8 000 дм
600 см = 6 м
30 дм = 3 м
2 км = 2 000 м
6 км 500 м = 6 500 м
12 000 мм = 12 м